Spin-Active and Magnetic Polymers - Boudouris, Bryan W.; Joo, Yongho (American Chemical Society, 2024)
Functional polymers have transformed, and continue to revolutionize, the materials landscape in monumental manners such that these advanced systems are put into critical products across a plethora of application arenas. Moreover, the field of polymer electronics has seen rapid and sustained growth over the last 30 years such that fundamental advances regarding the polymer chemistry and polymer physics of these macromolecules have led to transformational technologies. However, a related field has seen less attention, and that is the study of magnetic and spin-active polymers. While some research teams have made impressive strides in the realm of soft materials, the majority of the community has focused on inorganic and two-dimensional (2D) materials. In this Collection, we aim to (a) highlight recent publications in ACS Macro Letters that demonstrate the impressive foundational principles of the materials; (b) offer a means by which to introduce the broader readership to this area of study; and (c) encourage the community to submit their work to this effort such that the most exciting related research results are archived in a cohesive manner. We very much thank the American Chemical Society and the editorial team of ACS Macro Letters for providing us with an opportunity to facilitate the creation of a Collection that we anticipate will alter the polymer science arena. In this Collection, we have intentionally opened two distinct, but related, fields associated with the magneto-responsive and spin-responsive behavior of macromolecular systems. While the materials design paradigms for enhanced performance in either of these end-use spaces is distinct, there are clear points of synergy in coupling these avenues of research. Importantly, this Collection aims to stress the foundational principles associated with the chemistry, physics, and materials science of the polymers. While it is not unlikely that the structure？property relationship formulation could involve device fabrication and testbed characterization, works in this Collection will not include manuscripts whose primary intellectual merit is centered on device fabrication or performance optimization. Instead, we turn to the community to submit efforts that address underlying points regarding topics such as, but not limited to, (a) advanced archetypes for the synthesis of magnetic- and spin-active polymers; (b) the thermal, structural, and end-use properties of next-generation materials based on these macromolecules; (c) efforts that elucidate the unique interactions that arise due to coupling of polymers and magnetic fields; and (d) reports that detail the mechanism of spin transport in polymers. Addressing foundational questions such as these will continue to speed the progress in this exciting field that is building from a solid foundation, but a foundation that has significantly less literature associated with it than traditional organic electronics and polymer-based energy conversion and energy storage materials. In this context, we envision the following exemplary cases will encourage active discussion among disciplines, altogether expediting the advancement of such functional polymers in a constructive manner. These include molecular design and engineering strategies centered on spin-active and magnetic polymers, as highlighted by Delage-Laurin et al. in their work on the effectiveness of Faraday rotation and magneto-optical properties of polyferroceniums. (1) Similarly, the synthetic efforts recently made by Malech et al. and Alvaradejo et al. on the ring-opening metathesis of magnetic and/or spin monomers highlight how molecular design and advanced synthesis are critical to this community. (2,3) Another focus of this Collection is the structure？property relationship in spin and magnetic polymers. This is well exemplified by the recent work of Yu et al., which addressed the impact of structural variations on the paramagnetic or antiferromagnetic behavior of (poly)magnetic ionic liquids. (4) Additionally, Chan et al. and Costa et al. described the structural effects through the self-assembly of micellar nanoparticles in the development of diblock copolymers with pendant persistent organic radicals for magnetic resonance imaging (MRI) contrast agents. (5,6) Of course, we also encourage manuscripts based on theory and/or computation, as previous efforts have highlighted the power of these scholarly activities for the field. (7) By using this Collection as a means by which to pull the community together at this critical stage, we envision the rapid growth of the field over the next five years. That is, there is no reason why the growth trajectory of materials and applications associated with magnetic- and spin-active polymers cannot be on an even greater ascent than what occurred with electronic (e.g., conjugated) polymers and applications over the last three decades. This is because, in addition to the oft-recited advantages of solution-processable, low-cost polymer materials in the organic electronics regime, there are foundational material properties associated with soft polymeric materials that make them attractive relative to their inorganic counterparts for magnetic and spin applications. Thus, it is not a question of whether these materials will make significant inroads into applications such as quantum systems; instead, it is a question of the timing based on the appetite of the community to rally around these emerging materials and physics to speed the development in a deliberate manner. This Collection has that ability to initiate that steep climb. With this overarching point in mind, we also strongly encourage advanced data sharing efforts for manuscripts submitted to this effort such that the data and metadata associated with these publications are consistent with the findable, accessible, interoperable, and reusable (FAIR) principles. This open sharing of data will both allow for rapid validation of principles from other research teams and speed the development of the materials and principles using a combined computational and experimental approach. In this way, there is a wonderful opportunity for the community to rally for impressive and immediate impact to set the tone of science for this field. The organic electronics community historically has been one that brings together researchers from across the chemistry, physics, materials science, engineering, and biotechnology disciplines. Thus, the interdisciplinarity of the scientists and engineers that will push this exciting field forward is already established. History has shown that, as end-use applications have moved from transistors and light-emitting devices to energy conversion and energy storage systems and on to biomedical devices, the creativity and collaborative nature of folks in this polymer science arena is unlimited. Here, we applaud the researchers who have already taken the next step in this field, and we celebrate those who will contribute to this Collection through their own advancements and research accomplishments.